Fabrication And Characterisation Of Methylene Blue- Loaded Graphene Oxide And Reduced Graphene Oxide For Photodynamic Therapy Application - Ung, Yee Tze (2023)
Breast cancer is a common type of cancer diagnosed in women. The choice of treatment is important to reduce the morbidity and mortality rate. Photodynamic therapy (PDT) is one of the techniques introduced to treat diseases such as cancers by employing light-activated molecules known as photosensitisers to produce reactive oxygen species and subsequently inducing cancer cells apoptosis. As PDT is a non-invasive and targeted treatment, it provides advantages including lowering the potential side effects while improving the treatment efficiency. Graphene-based materials are getting more attention in pharmaceutical applications due to its attractive physicochemical properties including large surface area and easy modification for drug loading and targeting purposes. As the photosensitiser alone was unable to specifically target the breast cancer without causing cytotoxicity towards the normal cells, a suitable drug carrier to be able to control the release of the drug towards the breast cancer should be investigated. This study explores the effectiveness between graphene oxide (GO) and reduced graphene oxide (rGO) in the loading of methylene blue (MB) as well as the in vitro cytotoxic effect of GO-MB and rGO-MB on breast cancer cells. In this study, GO and rGO were synthesised through improved Hummers’ method and chemical reduction method respectively. The